Fluxes, vacua, and tadpoles meet Landau-Ginzburg and Fermat - Becker, Katrin; Gonzalo, Eduardo; Walcher, Johannes; Wrase, Timm (Journal of high energy physics, 2022)
Type IIB flux vacua based on Landau-Ginzburg models without Kähler deformations provide fully-controlled insights into the non-geometric and strongly-coupled string landscape. We show here that supersymmetric flux configurations at the Fermat point of the 19 model, which were found long-time ago to saturate the orientifold tadpole, leave a number of massless fields, which however are not all flat directions of the superpotential at higher order. More generally, the rank of the Hessian of the superpotential is compatible with a suitably formulated tadpole conjecture for all fluxes that we found. Moreover, we describe new infinite families of supersymmetric 4d $$ \mathcal{N} $$= 1 Minkowski and AdS vacua and confront them with several other swampland conjectures.